Visualising the past – An evaluation of processes and sequences for fingermark recovery from old documents. Issue 2 (March 2019) - Bleay, S.; Fitzgerald, L.; Sears, V.; Kent, T.
Abstract: This study aimed to collect data on the effectiveness of most of the fingermark visualisation reagents currently used on porous surfaces on fingermarks aged for up to 90 years, significantly extending the timescales for which such information exists. A limited subset of the variables associated with processing of old fingermarks was explored, with a focus on the use of 1, 8 diazafluoren-9-one (DFO), 1, 2-indandione, ninhydrin, and physical developer. These techniques were used in sequence on batches of cheques between 11 and 32 years old, and on documents dating from the 1920s and 1940s. The potential for applying a physical developer enhancement process (blue toning) as the final step in the sequence was also explored. The benefits of using processing sequences on porous items were clearly demonstrated, with all processes in the sequence adding value in terms of additional marks found on the cheques up to 32 years old. In addition, physical developer was found to be capable of developing fingermarks up to 90 years old, whereas the amino acid reagents appear less effective on documents of 70 years and older. An experimental physical developer formulation with reduced environmental impact was found to be as effective as the existing process in these experiments. Blue toning was found to visualise an additional 10–25% of marks, and its wider use after silver-based deposition processes is recommended based on the evidence from this study. Graphical abstract: Unlabelled Image Highlights: Investigation of fingermark processing sequences on documents up to 90 years old. 90 years old fingermarks were visualised using the physical developer process. A new physical developer formulation has performed well in comparative trials. Blue toning after physical developer reveals 10–25% additional marks. Sequential processing has demonstrated significant benefits on old documents.